Aspects of the ecology of the American grey squirrel Sciurus carolinensis gmelin in South Africa - Millar, James Christopher Gavin (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. in Nature Conservation) -- University of Stellenbosch, 1980.